Permanent crop cover as a strategy for drought-resistant viticulture: insights on how rhizosphere metagenomics influences leaf-level -omics for an enhanced overall plant response - Jáuregui, Iván; Ancín, María; García-Mina, José M.; Zamarreño, Angel M.; Iglesias-Sanchez, Ariadna; Florez-Sarasa, Igor; Aranjuelo, Iker (Frontiers in Plant Science, 2025)
The viticulture sector is currently threatened by climate change, impacting grape quality and yield through altered weather patterns and reduced soil health. The incorporation of cover crops can significantly bolster sustainability by enhancing soil moisture retention and structural integrity, both of which are essential for the enduring viability of vineyards in the long term. Cover cropping presents numerous advantages, such as the enhancement of soil health, mitigation of erosion, and facilitation of nutrient cycling; however, it may also pose certain short-term risks, including competition for vital resources like water. In spite of the progress made in comprehending the advantages of cover crops in vineyard settings, the intricate dynamics between plant–microbe interactions and the leaf-level metabolic responses of grapevines at the leaf level to drought conditions remain unexplored. This study examines the impact of water availability and green cover (comprising perennial ryegrass and Trifolium repens) on grapevine photosynthetic and metabolism efficiency, positing that crop cover fosters a microhabitat that bolsters microbial communities and drought resilience. Through comprehensive examinations of gas exchange, isotopic analysis, metabolomics, transcriptomics, and soil metagenomics, this study clarifies the relationships among irrigation methodologies, photosynthesis, and soil health, ultimately aiding in the fortification of agricultural resilience in the face of climate change. Our investigation demonstrates that the adoption of cover crops yields unexpected immediate benefits in bolstering drought resilience for vineyards. Despite an observed increase in overall evapotranspiration during drought conditions, the use of cover crops facilitated carbon accumulation and enhanced osmolyte-acting metabolites (including sugars and sugar alcohols) and abscisic acid (ABA) concentrations, alongside a comprehensive molecular adaptation to drought stress. Moreover, cover cropping was shown to promote the expression of defense-related pathways, while vineyards devoid of cover crops exhibited minimal transcriptional responses; certain taxa exhibited responses contingent upon the treatment, with Tistrellales and Gaiellales being linked to crop cover under favorable conditions, whereas Rhizoctonia demonstrated a strong association with rhizospheric soil during drought conditions when crop cover was present. Our study is the first to show that cover cropping can boost cash crop resilience to drought through intricate plant–soil–microbe interactions, providing benefits from the outset.